Sinuhes Flucht: Zu Religion und Literatur als Methode - Bommas, Martin (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
By using a new methodological approach which aims at identifying mythic and ritual structures in ancient Egyptian literary texts, this article aims at disclosing the cultural strategies applied in the relations between man and the sacred. In the story of Sinuhe, the sacred – generally marked by untouchability and unspeakabilty – is met with a spontaneous reaction leading to the precipitant flight of the protagonist. Different from previous scholarly research, this article does not propose a single reason for Sinuhe’s reaction but argues for a cultural pattern of behaviour instead.